2013
DOI: 10.1002/asia.201300594
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Supramolecular Behavior, and In Vitro Photodynamic Activities of Novel Zinc(II) Phthalocyanines “Side‐strapped” with Crown Ether Bridges

Abstract: Two new tetra- or di-α-substituted zinc(II) phthalocyanines 5 and 6 have been prepared through a "side-strapped" method. In the molecules, the adjacent benzene rings of the phthalocyanine core are linked at α-position through a triethylene glycol bridge to form a hybrid aza-/oxa-crown ether. The tetra-α-substituted phthalocyanine 5 shows an eclipsed self-assembly property in CH2Cl2 and the effect on the di-α-substituted analogue 6 is significantly weakened. Furthermore, the crown ethers of these compounds can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 84 publications
1
5
0
Order By: Relevance
“…In fact, the alkali- or alkaline-earth-metal-induced H aggregate is known to be the predominant form of aggregation of especially crown-substituted Pc due to the strong π–π interaction between Pc molecules, while metal- or solvent-induced J aggregation of Pc has been reported in only a few cases so far. The changes observed in the UV–vis and fluorescence spectra of P-CfZnPc originating from Be 2+ -induced J aggregation is quite similar to the metal- or solvent-induced J aggregation observed in previous studies. , The polymeric structure and Be 2+ -induced J-aggregated form of P-CfZnPc were also confirmed by MALDI-TOF mass spectra (Figure ), scanning electron microscopy (SEM) images of the spin-coated films of P-CfZnPc and its Be complex on glass (Figure ), and electrochemistry (discussed below).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…In fact, the alkali- or alkaline-earth-metal-induced H aggregate is known to be the predominant form of aggregation of especially crown-substituted Pc due to the strong π–π interaction between Pc molecules, while metal- or solvent-induced J aggregation of Pc has been reported in only a few cases so far. The changes observed in the UV–vis and fluorescence spectra of P-CfZnPc originating from Be 2+ -induced J aggregation is quite similar to the metal- or solvent-induced J aggregation observed in previous studies. , The polymeric structure and Be 2+ -induced J-aggregated form of P-CfZnPc were also confirmed by MALDI-TOF mass spectra (Figure ), scanning electron microscopy (SEM) images of the spin-coated films of P-CfZnPc and its Be complex on glass (Figure ), and electrochemistry (discussed below).…”
Section: Resultssupporting
confidence: 84%
“…The changes observed in the UV−vis and fluorescence spectra of P-CfZnPc originating from Be 2+ -induced J aggregation is quite similar to the metal-or solvent-induced J aggregation observed in previous studies. 73,75 The polymeric structure and Be 2+ -induced J-aggregated form of P-CfZnPc were also confirmed by MALDI-TOF mass spectra (Figure 9), scanning electron microscopy (SEM) images of the spin-coated films of P-CfZnPc and its Be complex on glass (Figure 10), and electrochemistry (discussed below).…”
Section: Spectroscopic Properties and Aggregationmentioning
confidence: 76%
“…Polypyrrole (PPy) nanoparticles are another class of conjugated polymers that exhibit high molar extinctions in the NIR and excellent photothermal conversion efficiencies. [175][176][177]180 Chen et al reported the synthesis of a strongly absorbing PPy nanoparticle with an extinction coefficient of 2.38 × 10 10 M −1 cm −1 at 808 nm, while conversion efficiency was 44.7%. 177 Using these nanoparticles, they were able to induce tumor cell kill by injecting PPy at a dose of 10 mg kg −1 and irradiating the area with 808 nm light (1 W cm −2 ; 5 min).…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Another reported approach to overcome Pc drawbacks as PS agent envisaged the chemical modification of Pc derivatives by developing novel synthetic routes and in order to tune Pc molecules aggregation and supramolecular organization [180,181]. Huang and collaborators [180] synthetized two ZnPc derivatives, a tetra-and a di-α-substituted ZnPc. A triethylene glycol (TEG) chain was used to form a hybrid aza-/oxa-crown-substituted phthalocyanine.…”
Section: Pcs-based Supramolecular Assemblies For Photodynamic Therapymentioning
confidence: 99%